PERANCANGAN MIXED USE BUILDING (APARTEMEN & RETAIL) DENGAN PENDEKATAN PERILAKU - Rose, Jessica Jannet (TERAKOTA : Jurnal Poster Arsitektur, Interior dan Rancang Kota, 2025)
DKI Jakarta is a bustling city and a residential hub for many people, including those in North Jakarta. One of the rapidly developing areas is Kelapa Gading, which has become a prime destination for workers seeking a place to live. However, Kelapa Gading is predominantly a high-end area, limiting housing options for the middle to lower-income population. To accommodate both migrant workers from other cities and native Jakarta residents, a strategic and comfortable living environment is essential—one that provides daily necessities within easy reach.Therefore, a mixed-use development with a behavioral approach is an ideal solution for workers in Jakarta. By integrating various functions, such as residential apartments and retail spaces, this type of development enables residents to meet their daily needs without relying on transportation to leave the premises. The application of architecture with a behavioral approach ensures that building functions align with user needs and lifestyles, fostering a dynamic yet comfortable living environment.